Burnout and coping perceptions of judo athletes throughout a sport season - Pires, D. A.; Ugrinowitsch, H. (Journal of Human Sport & Exercise, 2021)
This study aimed to investigate burnout and coping throughout a year of competition as well as to analyse the relationship between dimensions of burnout and coping strategies. Brazilian high-level judo athletes (N = 20) completed questionnaires of burnout and coping. Data collection occurred four times throughout a sport season. Although the results showed no increase in burnout dimensions, the confidence/motivation coping strategy increased during the season. Moreover, burnout dimensions showed a moderate and inverse correlation to confidence/motivation during the season.